Efficacy of Fungicides against Sclerotial Blight of Tea Plant - Bhagat, Indramani; Chakraborty, Bishwanath (Our Nature, 2014)
Tea, Camellia sinensis (L.) O. Kuntze is the most important hot beverage in the world today and one of the major cash crops of Nepal. Being a perennial, the tea plant possibly interacts with, more environmental problems than do most other plants. Sclerotial blight caused by Sclerotium rolfsii Sacc. is polyphagus fungal diseases which appears in the nursery grown tea seedlings. DOI: http://dx.doi.org/10.3126/on.v11i2.9601 Our Nature 2013, 11(2): 208-210